Brown Fat Fuel Utilization and Thermogenesis - Townsend, Kristy L. (2014)
Brown adipose tissue (BAT) dissipates energy as heat to maintain optimal thermogenesis and to contribute to energy expenditure, in rodents and possibly humans. The energetic processes executed by BAT require a readily available fuel supply, which includes glucose and fatty acids (FAs). FAs become available by cellular uptake, de novo lipogenesis, and from multilocular lipid droplets in brown adipocytes. BAT also possesses a great capacity for glucose uptake and metabolism, and an ability to regulate insulin sensitivity. These properties make BAT an appealing target for the treatment of obesity, diabetes and other metabolic disorders. Recent research has revealed a better understanding of the processes of fuel utilization carried out by brown adipocytes, which is the focus of the current review.